Effects of organic acids, chemical treatments and herbal essential oils on the vase life of cut carnation (Dianthus caryophyllus L.) flowers - Alkaç, Onur Sefa; Güneş, Mehmet; Belgüzar, Sabriye (Emirates Journal of Food and Agriculture, 2023)
Among the cut flowers, carnations are sensitive to ethylene. Therefore, the vase life is short and a negative situation arises in terms of marketing. Different chemical preservatives, herbal essential oils and growth regulators are used today to extend the post-harvest life of cut flowers. This study was conducted to determines the effects of single-use of some organic acids, chemical acids and essential oils and their combinations with sugar on postharvest life (vase life) of cut carnation flowers. Experiments were conducted in randomized plots design with three replications. Experimental treatments included: Salicylic Acid (100 mg/L), Ascorbic Acid (100 mg/L), Citric Acid (200 mg/L), Benzyl Adenine (50 mg/L), Carvacrol (200 mg/L), Thymol (200 mg/L) and sugar-supplemented (10 g/L) combinations of these treatments. Measured parameters included: Vase life, relative fresh weight, daily vase solution uptake, total vase solution uptake, pH change, bacteria population and diagnosis of dominant bacteria. Among the present treatments, 200 mg/L citric acid treatment decreased the bacteria population, prevented blockage in the plant's stem section, and thus, promoted water uptake. Thus, the best outcomes in terms of vase life, total vase solution uptake and relative fresh weights were achieved with 200 mg/L citric acid treatment. It was also observed that Salicylic Acid (100 mg/L) + Sucrose (10 g/L) and Benzyl Adenine (50 mg/L) + Sucrose (10 g/L) treatments yielded expected outcomes. Besides, non-sugar containing vase solutions yielded better outcomes than sugar-supplemented combinations. In terms of pH changes, decreases were observed in the final pH values of sugar-supplemented solutions compared to the initial pH values. Additionally, in present vase solutions, mostly Burkholderia cepacia species were diagnosed and also Pseudomonas antarctica, Pectobacterium carotovorum, Xanthomonas hortorum, Pseudomonas chlororaphis bacteria colonies were identified. As a result of the study, it is thought that 200 mg/L citric acid treatment and 100 mg/L salicylic acid + 10 g/L sugar treatment will contribute to cut flower and cut carnation producers and researchers working in this in the post-harvest field. Keywords: Bacteria; Benzyl adenine; Citric; Environment-friendly; Sugar